Afrika Zamani: n°20 & 21, 2012-2013 - Full Issue - Journal System, (Afrika Zamani, 2021)
Contents Metissage in Nineteenth Century Senegal: Hybrid Identity and French Colonialism in a West African Town Hilary Jones ..................................................... 1 Musical Hybridity in Flux: Representing Race, Colonial Policy, and Modernity in French North Africa, 1860s-1930s Jann Pasler ......................... 21 Des cow-boys dans la savane : cinéma et hybridation culturelle en contexte colonial Odile Goerg ............................................................................. 69 A la recherche d’un primitivisme fédérateur : le peintre Atlan et le groupe Cobra Anissa Bouayed ...................................................................... 95 Colonial Encounters: A Danish Planter in German East Africa Marianne Rostgaard ......................................................................................... 107 Affirmation d’une identité afro-portugaise et éducation en Casamance fin du XIXe siècle début XXe siècle Céline Labrune-Badiane ................................................. 131 Camwood (Pterocarpus Tinctorius) in the Political Economy of the Cross and Manyu Rivers Basin of Cameroon and Some Hinterland Communities, 1916-1961 Henry Kam Kah ....................................... 149 Colonial Economic Disempowerment and the Responses of the Hlengwe Peasantry of the South East Lowveld of Zimbabwe: 1890-1965 Taderera Hebert Chisi .................................................................. 165